Differential induction of defense related enzymes involved in lignin biosynthesis in wheat in response to spot blotch infection - and D.V. SINGH, SOMA DAS, RASHMI AGGARWAL* (Indian Phytopathology, 2003)
Spot blotch of wheat caused by Bipolaris sorokiniana is prevalent in wheat growing areas of northern India. The role of lignification and the enzymes involved in the biosynthesis of lignin i.e. phenylalanine ammonia-lyase (PAL), cinnamyl alcohol dehydrogenase (CAD) and peroxidase (POX) in the wheat spot blotch disease resistance was studied using a resistant (Pusa-T 3336) and a susceptible genotype (Agra local). PAL activity began to increase in both the genotypes at 12 h after inoculation and reached to maximum at 2 days after inoculation (DAI). In resistant genotype Pusa-T 3336, 30 fold increase was found at 12 h after inoculation, whereas in susceptible genotype Agra local, the activity was marginal. CAD and POX activities were maximum at 2 DAI in resistant genotype, but in Agra local maximum CAD and POX activity was found at 4 DAI. POX activity was six times more in Pusa-T 3336 than Agra local. High lignification was observed in the resistant genotype.